THE EFFECT OF THE INFLATABLE METHOD ON THE PAIN SCALE OF LABOR AT STAGE I - Oktapiani, Putri; Susanti, Eva; Febrina, Lydia (International Journal of Multidisciplinary Research and Literature, 2024)
Labor pain is a problem that mothers complain about in normal labor. Some of these pains often make mothers frustrated and desperate so some of them have alternative actions such as Sectio Caesarea surgery to avoid suffering from pain in labor. The purpose of this study was to determine the effect of the Inflatable Method on the Pain Scale of Stage I Labor. Methodology: This study used a quantitative approach with the Quasi-Experimental method using the Pre-Post Test with Control Group design. The population of this study consisted of first-time laboring mothers who fit the sampling criteria using the accidental sampling technique, with a sample size of 54 respondents. The analysis used the Wilcoxon Signed Ranks Test and Mann-Whitney Test. The data collection instrument is observation through the Numeric Rating Scale format. Results: it was found that the average pain scale of laboring mothers before the intervention of the Blow-Off Method was 6.89 and after the intervention of the Blow-Off Method was 4.89. The results of the statistical tests showed that the blow-off method affected the Pain Scale of Labor Period I (p = 0.000). This research is expected to be used by respondents in the process of childbirth with minimal trauma. Conclusion: There is a decrease in pain levels in the intervention group and control group after treatment with a value of p <0.05